Potential application of gasification to recycle food waste and rehabilitate acidic soil from secondary forests on degraded land in Southeast Asia. (1st May 2016) - Yang, Zhanyu; Koh, Shun Kai; Ng, Wei Cheng; Lim, Reuben C.J.; Tan, Hugh T.W.; Tong, Yen Wah; Dai, Yanjun; Chong, Clive; Wang, Chi-Hwa
Abstract: Gasification is recognized as a green technology as it can harness energy from biomass in the form of syngas without causing severe environmental impacts, yet producing valuable solid residues that can be utilized in other applications. In this study, the feasibility of co-gasification of woody biomass and food waste in different proportions was investigated using a fixed-bed downdraft gasifier. Subsequently, the capability of biochar derived from gasification of woody biomass in the rehabilitation of soil from tropical secondary forests on degraded land (adinandra belukar) was also explored through a water spinach cultivation study using soil-biochar mixtures of different ratios. Gasification of a 60:40 wood waste-food waste mixture (w/w) produced syngas with the highest lower heating value (LHV) 5.29 MJ/m 3 —approximately 0.4–4.0% higher than gasification of 70:30 or 80:20 mixtures, or pure wood waste. Meanwhile, water spinach cultivated in a 2:1 soil-biochar mixture exhibited the best growth performance in terms of height (a 4-fold increment), weight (a 10-fold increment) and leaf surface area (a 5-fold increment) after 8 weeks of cultivation, owing to the high porosity, surface area, nutrient content and alkalinity of biochar. It is concluded that gasification may be an alternative technology to food waste disposal through co-gasification with woody biomass, and that gasification derived biochar is suitable for use as an amendment for the nutrient-poor, acidic soil of adinandra belukar. Graphical abstract: Highlights: Co-gasification of wood waste and food waste in different ratios was investigated. Increasing the food waste proportion increases the heating value of the syngas. Biochar was able to rehabilitate nutrient-poor and acidic soil from degraded land. Water spinach cultivated in a 2:1 soil-biochar mixture grew best.